MODELLING IN SIMPLE BEAM STRUCTURE WITH SAP 2000 AND AUTODESK RSA PROFESSIONAL - sedayu, agung (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
A simple beam is one application of determinate static structure components. The static structure is a structure that can be solved by a determinate static basic equation. This study aims to create a simple beam model which is then analyzed using two software contain SAP 2000 Version 11 Nonlinear and Autodesk RSA Professional 2012. The results of both modelings can be compared with some different steps in both software. Simple beam modeling with the two software results in the same reaction value for the point and distributed loads. By comparing three stages of completion of a simple beam structure with two different cases are point and distributed loads produce the same support reactions. Analysis with SAP 2000 and Autodesk RSA Pro software can complete the structure more easily and quickly.